PS 11-13 IMPACT OF MALNUTRITION AND MARKERS OF VASCULAR CALCIFICATION ON THE LEFT VENTRICULAR HYPERTROPHY IN HEMODIALYSIS PATIENTS. (September 2016) - Nakagawa, Naoki; Maruyama, Keisuke; Matsuki, Motoki; Sato, Nobuyuki; Hasebe, Naoyuki
Abstract : Objective: This study investigated the impact of malnutrition and various markers of vascular calcification on left ventricular hypertrophy (LVH) in hemodialysis patients. Design and Method: We recruited 60 hemodialysis patients (43 men and 17 women, mean age: 64.5 ± 12.6 years), and measured their serum fetuin-A, osteoprotegerin, osteopontin, arterial stiffness, and echocardiographic parameters, and then analyzed the relationships of these variables. The geriatric nutritional risk index (GNRI) was used to assess the nutritional status of the patients and was calculated using the following formula: GNRI = (14.89 × serum albumin) + [41.7 × (body weight/body weight at BMI of 22)]. Malnutrition was defined as GNRI ⩽96 based on our previous report (Nakagawa N, et al. Ther Apher Dial. 19:30–39, 2015). Results: Mean systolic blood pressure was 144.7 ± 23.2 mmHg, mean pulse pressure 69.1 ± 19.9 mmHg, mean GNRI 94.6 ± 8.0, mean brachial-ankle pulse wave velocity (baPWV) 2132 ± 607 cm/s, and mean LV mass index (LVMI) 126 ± 39 g/m 2 . GNRI was significantly and positively correlated with fetuin-A, and negatively with age, pulse pressure, osteopontin, baPWV, LVMI, and E/E'. When GNRI was divided at 96, the patients with lower GNRI had significantly lower fetuin-A, and higher osteoprotegerin, LVMI and baPWV compared with those with higher GNRI. In a stepwise multiple regression analysis, GNRI was an independent determinant of LVMI (β = −0.455, P = 0.002) after adjusting for age, pulse pressure and hemoglobin. Malnutirition positively reflected an increased vascular stiffness leading to an aggravation of LVH. Conclusions: Malnutrition was independent determinants of LVH in association with fetuin-A, osteopontin and vascular stiffness, suggesting that the assessment and improving the nutritional status are important for retarding the progression of LVH through mediating the balance of the tissue calcification regulators in hemodialysis patients.